The use of augmented-reality technology to improve judo techniques. Premises, assumptions, methodology, research tools, preliminary scenarios - the first stage of the study - Witkowski, K.; Sobecki, J.; Maslinski, J.; Cieslinski, W. B.; Rokita, A.; Kalina, R. M. (Archives of Budo, 2016)
Background and Study Aim: Sport, professionally and for all, is an area of both the application of modern technology, and to create new ones. The premises of such a statement is to protect health (all practitioners sport) and to achieve optimal sport results first of all by top athletes. In judo, like in each combat sports, motoric actions are cumulative directly on the body of an athlete during a specific exercise (kata, uchi komi etc.), training fights (randori) and the tournaments ones. The aim of this work are the most important premises based on the analysis of the available technology, augmented reality (AR) in relation to the expectations of adaptive judo athletes (under the scientific knowledge about the determinants of success) and assumptions construction of research tools and training, including initial scenarios.